A survey of piezoelectric actuators with long working stroke in recent years: Classifications, principles, connections and distinctions. (15th May 2019) - Wang, Shupeng; Rong, Weibin; Wang, Lefeng; Xie, Hui; Sun, Lining; Mills, James K.
Highlights: We introduce the piezoelectric actuators with long working stroke in recent years. The pros and cons for actuators and the transformation relationships are discussed. The clamping mechanisms are classified into intermittent type and continuous type. Abstract: The development of piezoelectric actuation, starting from single-layer materials with the converse piezoelectric effect, then progressing to multilayer piezo-stack actuators, amplified actuators, non-resonant stepping actuators, and resonant ultrasonic actuators, researchers have been developing methodologies to expand the output displacement of the piezoelectric materials. With these developments, the working stroke of the piezoelectric actuators has been increased from the micrometer-scale to the millimeter-scale, then to the centimeter-scale, or even without limit. There are both obvious distinctions and close connections among these approaches. In this paper, we summarize and classify these approaches systematically. Centering around the long working stroke, we not only discuss the pros and cons for each type, but also explore the derivative relations among these principles. Particularly the stepping actuators, by replacing the clamping mechanism, the inchworm actuator, seal actuator and inertial actuator can transform into each other. The structure of this paper aids in understanding the piezoelectric actuators clearly. Moreover, this paper is also beneficial for determining suitable designs, applicable fields and potential directions for future breakthroughs in technology.